IL-10+CD19+ regulatory B cells induce CD4+Foxp3+regulatory T cells in serum of cervical cancer patients - Chunfeng Yang; Yuanyuan Zhang; Rui Wang; Bing Cheng; You Wu; Xi Fu (Taylor & Francis Group, 2024)
AbstractIncrease of regulatory T cells (Tregs) in the tumour microenvironment predicts worse survival of patients with various types of cancer. Recently, B cells play a significant role in the maintenance of Treg cells. However, the relevance of regulatory B cells (Bregs) to tumour immunity in humans remains elusive. Flow cytometry analysis was used to detect the Bregs and Tregs. Double staining results illustrated that the proportion of Bregs and Tregs were prominently higher in cervical cancer than normal tissues. Increase of Bregs and Tregs in cervical cancer microenvironment was associated with poor survival. Furthermore, Bregs cocultured with cervical cancer cell lines increased and induced Tregs. To sum up, the increased expression of Bregs contributes to the differentiation of CD4+ T cells into Tregs in the cervical cancer.